A nonsense mutation in MME gene associates with autosomal recessive late‐onset Charcot–Marie–Tooth disease - Zeinab Jamiri; Rana Khosravi; Mohammad Mehdi Heidari; Ebrahim Kiani; Javad Gharechahi (Molecular Genetics & Genomic Medicine, 2022)
Abstract Background The genetic cause for the majority of patients with late‐onset axonal form of neuropathies have remained unknown. In this study we aimed to identify the causal mutation in a family with multiple affected individuals manifesting a range of phenotypic features consistent with late‐onset sensorimotor axonal polyneuropathy. Methods Whole exome sequencing (WES) followed by targeted variant screening and prioritization was performed to identify the candidate mutation. The co‐segregation of the mutation with the phenotype was confirmed by Sanger sequencing. Results We identified a nonsense mutation (c.1564C>T; p.Q522*) in membrane metalloendopeptidase (MME) gene as the cause of the disease condition. The mutation has a combined annotation‐ dependent depletion (CADD) score 45 and predicted to be deleterious based on various algorithms. The mutation was inherited in an autosomal recessive mode and further confirmed to co‐segregate with the disease phenotype in the family and showed to has the required criteria including rarity and deleteriousness to be considered as pathogenic. Conclusion The MME gene encodes for the membrane bound endopeptidase neprilysin (NEP) which is involved in processing of various peptide substrates. The identified mutation causes a complete loss of carboxy‐terminal region of the NEP protein which contains the zinc binding site and the catalytic domain and thus considered to be a loss‐of‐function mutation. The loss of NEP activity is likely associated with impaired myelination and axonal injury which is hallmark of CMT diseases.